What will it take to improve the characterisation of deep mineral deposits in order to assess "economic value" early in the discovery process?. Issue 1 (1st December 2019) - Cucuzza, Joe
Summary: In Australia, in particular, the consensus is that most, if not all, of the world-class non-ferrous mineral deposits that are either at or near the surface have been found. This means that we need to look deeper in the new greenfield search space characterised by thicker post-mineralisation cover. But in doing so the technical and financial risk increase considerably. One way of reducing the risk to be able to make an assessment of the "economic value" of any deep orebody much earlier in the discovery process. But what will it take to be able to achieve this? The answer lies in improving existing geophysical technology and applying it in novel ways, developing more effective 3D multi-modal inversions tightly calibrated to all available geological facts, and the application of machine learning approaches that permit robust assessment of uncertainty.